Observational study to assess prescription cost and its relation to the socioeconomic status of the patients in psychiatry outpatient department in a tertiary care hospital - Goyal, Sumit G.; Kurle, Dnyaneshwar G.; Samant, Balwant D. (International Journal of Basic & Clinical Pharmacology, 2016)
Background: To analyse the cost of prescriptions and to determine the relationship between socioeconomic status of the patients and the cost of prescriptions. Methods: A prospective, observational study was conducted in psychiatry OPD of a tertiary care hospital from August 2007 to January 2008. 300 patients of either sex and irrespective of age suffering from mental disorders were included. Information about the socioeconomic status of the patient was analysed on the basis of Kuppuswami’s socioeconomic status scale (updated for 2007). Cost analysis (calculated for 30 days) was done by calculating (a) average cost of the prescription borne by the hospital (b) average cost of the prescription borne by the patient and (c) average total cost of the prescription. The correlation between the socioeconomic score of the patients with the above three cost parameters was carried out using the Spearman rank correlation. Results: In a cohort of 300 patients, 61.3% patients belong to upper lower class. Cost analysis showed that the average total cost of the prescription was 121.97 INR of which average cost of the prescription borne by the hospital and the patients was 18.43 INR and 103.54 INR respectively. The total cost of the prescription and cost of prescription borne by the patient had a positive correlation with the socioeconomic score of the patient, while the cost of prescription borne by the hospital was inversely correlated with the socioeconomic score of the patient. Conclusions: It seems that the prescribing decision was influenced by the socioeconomic status of the patients.